VD_FINDINFO Ord / 2012 / 14 vom 28. September 2012 - VD Tribunal cantonal (2012)
RESTITUTION DE L'EFFET SUSPENSIF, RETRAIT DE L'EFFET SUSPENSIF | 97 al. 1 LAVS, 54 al. 1 let. c LPGA, 55 al. 2 PA, 55 al. 3 PA, 55 al. 4 PA